2001
DOI: 10.1038/labinvest.3780350
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Hybridization of Microdissected Familial Ovarian Carcinoma: Two Deleted Regions on Chromosome 15q Not Previously Identified in Sporadic Ovarian Carcinoma

Abstract: SUMMARY:The vast majority of familial ovarian cancers harbor a germline mutation in either the breast cancer gene BRCA1 or BRCA2 tumor suppressor genes. However, mutations of these genes in sporadic ovarian cancer are rare. This suggests that in contrast to hereditary disease, BRCA1 and BRCA2 are not commonly involved in sporadic ovarian cancer and may indicate that there are two distinct pathways for the development of ovarian cancer. To characterize further differences between hereditary and sporadic cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Deletion of 22q13 is common in ovarian, breast and colorectal cancer. 24,25 Overall, chromosomal losses were more frequent than were chromosomal gains in the leiomyosarcoma area, similar to that which has been reported previously in uterine leiomyosarcomas. 26 The amplification of additional chromosomal foci, including that for Myc, was observed in leiomyosarcoma areas.…”
Section: Discussionsupporting
confidence: 74%
“…Deletion of 22q13 is common in ovarian, breast and colorectal cancer. 24,25 Overall, chromosomal losses were more frequent than were chromosomal gains in the leiomyosarcoma area, similar to that which has been reported previously in uterine leiomyosarcomas. 26 The amplification of additional chromosomal foci, including that for Myc, was observed in leiomyosarcoma areas.…”
Section: Discussionsupporting
confidence: 74%
“…Although several studies related to somatic CNVs of tumor DNAs previously reported that BRCA1-associated ovarian cancers show a higher frequency of somatic CNVs than sporadic ovarian cancers (Patael-Karasik et al, 2000;Zweemer et al, 2001;Israeli et al, 2003;Ramus et al, 2003;Walsh et al, 2008), differences in genetic CNV background between BRCA1 and sporadic groups have received little discussion. This study shows that genomic profiles of CNV in BRCA1 carriers are qualitatively distinct from those in sporadic ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 97%
“…Histologically, most BRCA1-associated ovarian cancers are serous papillary adenocarcinomas (Sekine et al, 2001). Interestingly, the genomic profile for BRCA1-associated ovarian cancer is distinct from that for sporadic ovarian cancer, although they have the same histological type (Patael-Karasik et al, 2000;Zweemer et al, 2001;Israeli et al, 2003;Walsh et al, 2008). Therefore, it is thought that BRCA1-associated and sporadic serous ovarian cancers arise from different molecular pathways (Walsh et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…15 Interestingly, deletions of the relevant region of chromosome 15 have been described in human ovarian carcinomas, 52 which suggests that the region of chromosome 15 in which the IRP2 gene is found may be somewhat prone to deletion. Although we did not find elevated red cell protoporphyrin IX levels in IRP2 ϩ/Ϫ mice, it is possible that homozygous IRP2 deletions or mutations will be the cause of some forms of refractory anemia in humans, particularly if protoporphyrin IX levels are elevated and there is late-onset neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%